مقدمہ کتاب سیرۃ النبی ﷺ کا تجزیاتی مطالعہ - Farida Kakar; Dr. Naseem Akhter; Rana Mudser (الآفاق اسلامی و تحقیقی مجلہ, 2024)
The Prophet Mohammad (SAW) is acknowledged as the greatest mentor of all times. A lot of research work with blend of devotion and dedication has so far been under taken several research scholars in the area of Seerah writings. It is the miraculous feature of noblest Personality of Prophet Mohammad (SAW) that the followers of different religions, irrespective of religious bindings have produced master piece of writing, in this context every contributor tried to imbibe and disseminate pearls of knowledge, affection and sacred attachment with Prophet of Islam (SAW) according to their capacity and potential. Among the shining stars of Seerah Writing the contribution of Allama Shibli Numani has been acknowledged as the great pioneer Seerah Writer. He collected abundant of data about Seeraat-un-Nabi (SAW) and wrote a book '' Seerat-un-Nabi (SAW) in Urdu. In this article very important discussions of Seerah Writing in'' Seerat-un-Nabi'' were taken into consideration like importance of Seerah Writing, starting of Seerah Writing, discussion on of Seerah Arts, European publications and their joint principles.